1998
DOI: 10.1016/s0022-5223(98)70461-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimal flow rates for integrated cardioplegia

Abstract: Tepid retrograde cardioplegia resulted in an accumulation of toxic metabolites. The addition of antegrade vein graft infusions at a flow rate of 100 ml/min resulted in a washout of these metabolites. A flow rate of 200 ml/min further improved this washout and resulted in improved ventricular function. An integrated approach to myocardial protection using a flow rate of 200 ml/min may improve the results of coronary bypass surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In patients with hypoplastic aortic arch, we use the dual arterial Y-connected perfusion technique to maintain myocardial perfusion (WBH) at the same high flow rate as cerebral perfusion, with mean coronary perfusion pressure being monitored at the root of the aortic artery. We believe that higher flow rates result in better myocardial protection (16)(17)(18), especially for heart with LVH. Mean coronary perfusion pressure was 10-20 mm Hg higher than the right radial artery pressure and maintained 60-70 mm Hg when blood flow was regulated at 50-75 mL/kg/min.…”
Section: Discussionmentioning
confidence: 94%
“…In patients with hypoplastic aortic arch, we use the dual arterial Y-connected perfusion technique to maintain myocardial perfusion (WBH) at the same high flow rate as cerebral perfusion, with mean coronary perfusion pressure being monitored at the root of the aortic artery. We believe that higher flow rates result in better myocardial protection (16)(17)(18), especially for heart with LVH. Mean coronary perfusion pressure was 10-20 mm Hg higher than the right radial artery pressure and maintained 60-70 mm Hg when blood flow was regulated at 50-75 mL/kg/min.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, because of reasons such as slow flow rate, heterogeneous distribution, and poor protection of the right ventricle wall, the use of the retrograde cardioplegia method on its own is also restricted. For this reason, the use of the antegrade and retrograde cardioplegia methods together can increase its efficacy [6,9]. The aim in using antegrade and retrograde cardioplegia in combination is to supplement each other.…”
Section: Discussionmentioning
confidence: 99%
“…The inability to eliminate anaerobic metabolism by increasing the flow rates prompted us to focus on the temperature of the cardioplegia solution and on supplementing continuous retrograde cardioplegia with intermittent antegrade cardioplegia. In a series of randomized clinical trials, 30–33 we were able to decrease myocardial lactate release by delivering tepid (29°C) cardioplegia. We observed that anaerobic metabolism begun after 7 minutes of warm ischemia and after 13 minutes of tepid ischemia.…”
Section: Myocardial Protection—1 Retrograde Cardioplegiamentioning
confidence: 99%
“…Adequate visualization of the distal anastamoses can be achieved by stopping cardioplegic delivery for up to 13 minutes without inducing anaerobic metabolism with tepid temperatures. The simultaneous technique of combined cardiplegia keeps the heart decompressed and vented, washes atheroemboli from patent veins and arteries, and provides uniform myocardial protection 30,31 …”
Section: Myocardial Protection—1 Retrograde Cardioplegiamentioning
confidence: 99%